Mengeksplorasi Peran Komunikasi dalam Meningkatkan Wisata Gastronomi di Madura - Suryandari, Nikmah; Farida Nurul Rahmawati; Ferry Adhi Dharma (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2024)
This article examines the increasing popularity of gastronomic tourism, which emphasizes the opportunity to taste local cuisine and get to know its gastronomic traditions. What is the value of efficient communication in enhancing the gastronomic tourism experience in terms of language, culture and cuisine. The growing importance of social media for connecting travelers with local communities is explained in this article. The purpose of this paper is to find out how communication can improve the culinary tourism experience in Madura. Tourists who have the opportunity to interact with the community will better appreciate the local way of life and culinary delights. The research design used is descriptive qualitative. The informants in this research are tourists who visit Madura and managers of culinary and gastronomic tourist attractions in this region. The results show that tourists who visit Madura obtain information about tourist destinations from the media and have positive experiences while traveling. Managers of culinary and gastronomic tourist attractions have not utilized communication media optimally due to technical obstacles. A sustainable and responsible gastronomic tourism policy is a positive recommendation for the development of gastronomic tourism in this region.